Genetic variation of maiden lily (Lilium rubellum Baker) within and among three natural populations in Fukushima Prefecture in Japan - Castro, M. (2019)
Lily (genus Lilium) is one of the most important flowers for bulb and cut flower production in the world. Lilium rubellum Baker is a native species of Japan that exhibits early flowering, is pink coloured, and possesses a pleasant fragrance, which makes it an important genetic resource for breeding lilies. In this work, the genetic diversity of L. rubellum was studied among three natural populations located in Fukushima Prefecture, Japan, which have been designated as the Mt. Azuma, Nango and Atsushio-kano populations. A total of 31 accessions collected in 1997 were analysed using Random Amplified Polymorphic DNA (RAPD) markers. Eighteen decamer primers produced 98% polymorphic RAPD bands; furthermore, 11 of the 18 primers produced 10 or more polymorphic bands with a mean per primer Polymorphic Information Content of 0.382. Among the three populations, the mean Shannon index, Nei´s gene diversity and percentage of polymorphic loci were 0.2749, 0.4099 and 76.7%, respectively. These data revealed that there is a high genetic diversity within all the populations. Analysis of the three genetic diversity indices within populations showed that the Nango population had the highest genetic diversity, whereas the Atsushio-kano population had the lowest. An unweighted pair group method with arithmetic mean dendrogram based on Jaccard´s similarity coefficient was constructed, and the three populations of L. rubellum collected in the Fukushima prefecture were clearly differentiated at 0.61 similarity index. The Nango and Mt. Azuma populations were genetically closer than the Atsushio-kano population. The analysis of molecular variance showed a 29.53% variance among the populations. This study revealed that there is high genetic diversity within populations and moderate genetic diversity among the three natural populations of L. rubellum Baker in the Fukushima Prefecture of Japan.